Colonization as myth-making - Jackson, Moana (Being indigenous: perspectives on activism, culture, language and identity, 2019)
Keywords: colonisation; crown; ethnic identity; government; land loss; land theft; political power; rangatiratanga; tiriti o waitangi/treaty of waitangi

Chapter 40: Indigenous finance: treaty settlement finance in Aotearoa New Zealand - Bargh, Maria (The handbook of diverse economies, 2020)
"Theorising and illustrating diverse, more-than-capitalist economies, this broad-ranging Handbook presents ways in which it is possible to imagine and enact other ways of being. It gathers together empirical examples of diverse economic practices and experiments from across the world, framed by in-depth discussions of key theoretical concepts. Organised into thematic sections, the Handbook moves from looking at diverse forms of enterprise, to labour, transactions, property, and finance as well as decentred subjectivity and diverse economies methodology. Chapters present a wide diversity of economic practices that make up contemporary economies, many of which are ignored or devalued by mainstream economic theory. Pushing the boundaries of economic thinking to include more than human labour and human/non-human interdependence, it highlights the challenges of enacting ethical economies in the face of dominant ways of thinking and being. Economic geography, political economy and development studies scholars will greatly appreciate the empirical examples of diverse economic practices blended with theory throughout the Handbook. It will also benefit policy-makers and practitioners working within diverse economies, or looking to create more ethical ways of living"-- Provided by publisher.
Keywords: colonisation; economic aspects; governance; land loss; land ownership; tiriti o waitangi/treaty of waitangi; treaty settlements

Settler violence, family, and whānau violence in Aotearoa New Zealand - McIntosh, Tracey (Women, Crime and Justice in Context: Contemporary Perspectives in Feminist Criminology from Australia and New Zealand, 2022)
This chapter looks at the impact on M?ori that colonial and neo-colonial practices of dispossession and immiseration have had on elevated family violence rates in Aotearoa New Zealand. In reflecting on interpersonal violence, it seeks to locate systemic forms of violence, such as legislative violence, institutional violence, and economic violence, and their relationship with family violence. It draws on David Nixon’s (2011) notion of slow violence to look at the intergenerational harm of poverty, racism, and entrenched negative social issues. The focus then moves to Indigenous solutions to family violence that demonstrate the power of lived experience and social and cultural expertise to support healing and transformation in M?ori communities.
Keywords: crown policy; crown violence; dispossession; family violence; intergenerational trauma; land loss